Grammar Mistakes of Engineering Students’ Research Titles Writing in English - Suci Tresna Dewi Handayani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
In a research context, a research title is usually translated into English to provide appropriate understanding for all readers. However, grammar mistakes in translating it often occur. This research focuses on the grammar mistakes found in research titles (English version) of Engineering students at one of the universities in West Java. This research focuses on 105 Engineering students’ research titles data and answers questions of what are the grammar mistakes found, and what are the students’ perceptions regarding the process of translating their titles. By analyzing the titles data, this research found that, out of 105 titles, there are 93 titles with grammar mistakes. These consist of excessive use of definite articles in 69 titles, improper use of prepositions in 22 titles, and improper phrases in 33 titles. Then, the Engineering students’ perceptions about their titles’ translating process were gained from interviews to 5 of them. They were worried about translating it themselves due to their limited understanding of English which made them rely more on translation machines such as Google Translate and ChatGPT without the process of reviewing the translation results’ meaning. The process of reviewing and increasing motivation that builds enthusiasm for learning grammar are needed.